2013
DOI: 10.1002/2013jd020341
|View full text |Cite
|
Sign up to set email alerts
|

Urban measurements of atmospheric nitrous acid: A caveat on the interpretation of the HONO photostationary state

Abstract: [1] Numerous studies infer the existence of an "unknown" daytime HONO source based on the assumption that HONO is at photostationary state (PSS). Secondary HONO production rate as high as 1.1 ppb hr À1 can be estimated from this approach, based on measurements made during the Study of Houston Atmospheric Radical Precursors campaign in May of 2009. We argue, however, that the PSS assumption might not have been valid because the transport time from nearby NO x emission sources to the measurement site was likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 40 publications
(35 reference statements)
7
43
1
Order By: Relevance
“…This equilibrium can only explain a minor portion of gas phase HONO observed at remote and rural sites (Kleffmann, 2007;Su et al, 2008b;Sörgel et al, 2011a;Wong et al, 2012) but may play an important role in measurement results obtained in urban areas (Lee et al, 2013). The budget calculations of Sörgel et al (2011a) and Li et al (2012) showed that including heterogeneous reactions of NO 2 (R4) only slightly improves the discrepancy between [HONO] PSS and measured HONO mixing ratios.…”
Section: R Oswald Et Al: Comparison Of Hono Budgets For Two Measurementioning
confidence: 96%
See 1 more Smart Citation
“…This equilibrium can only explain a minor portion of gas phase HONO observed at remote and rural sites (Kleffmann, 2007;Su et al, 2008b;Sörgel et al, 2011a;Wong et al, 2012) but may play an important role in measurement results obtained in urban areas (Lee et al, 2013). The budget calculations of Sörgel et al (2011a) and Li et al (2012) showed that including heterogeneous reactions of NO 2 (R4) only slightly improves the discrepancy between [HONO] PSS and measured HONO mixing ratios.…”
Section: R Oswald Et Al: Comparison Of Hono Budgets For Two Measurementioning
confidence: 96%
“…Horizontal transport (T h ) can strongly influence budget calculations in urban regions (Lee et al, 2013). However, Hyytiälä is surrounded by a uniform boreal forest with up to 95 % of the area within a 5 km radius being forested, with mostly Scots pine and spruce creating a homogenous fetch.…”
Section: Hono Budget Calculationsmentioning
confidence: 99%
“…In this approach, the sources and sinks of the species in question are assumed to balance each other and is thus only suitable for species with a short lifetime, such as free radicals. However, it has been widely used to study the daytime HONO budget, despite its lifetime being in the range of 10-20 min during the day Wong et al, 2012), resulting in significant uncertainties, especially for measurements close to emission sources (Lee et al, 2013). However, the measurement site in this study is described as an urban background site and thus is relatively free from the influence of major roads or point sources.…”
Section: Hono Photostationary State Approachmentioning
confidence: 99%
“…However, concentrations are not only controlled by the local ground surfaces source processes but also depend on the convective mixing in the atmosphere, leading to a potential misinterpretation of the correlation results. In addition, the assumed PSS conditions may also not be fulfilled when HONO and its precursors were measured close to their sources (Lee et al, 2013;Crilley et al, 2016).…”
Section: S Laufs Et Al: Diurnal Fluxes Of Hono Above a Crop Rotationmentioning
confidence: 99%